1901 N J. Laws 265, ch. 120, § 14. - (:unkn) unknown (General Publisher, 1901)
It shall be unlawful to hunt with a hound or hounds, or with fire-arms or weapons of any kind, or to carry a gun in the woods or fields or on the waters on the Sabbath day, commonly called Sunday, under a penalty of twenty dollars for each offence.
--
Keywords: HUNTING REGULATION